Formation of a single poly(N, N-diethylacrylamide) micro-droplet in water by coupling of photothermal effects and an optical force. (May 2019) - Matsumoto, M; Asoh, T; Shoji, T; Nishiyama, T; Horibe, Hideo; Katsumoto, Yukiteru; Tsuboi, Yasuyuki
Abstract: Poly( N -isopropylacrylamide) (PNIPAM) exhibits phase separation with lower critical solution temperature (LCST). In the 1990s, Masuhara and co-workers reported the first demonstration of optical trapping of PNIPAM forming a micrometer-sized polymer droplet. Since then, this technique has attracted much attention to create a molecular assembly in a microspace. In the present study, we targeted poly( N, N -diethylacrylamide) (PDEA), which has an analogous chemical structure to PNIPAM. We demonstrated that optical tweezers formed the unique micro-morphologies of a phase separated PDEA droplet. Fluorescence microscopic images and Raman spectra of the PDEA droplet showed that a lot of smaller-sized water-rich micro-domains were inhomogeneously formed in the droplet. Such unique phase separation behavior was never observed in steady-state heating of an aqueous PDEA solution above its LCST. Our results indicate that a novel micro-structure can be formed by coupling of an optical gradient force and a local temperature elevation.